PERTUMBUHAN PERUSAHAAN, PROFITABILITAS DAN UKURAN PERUSAHAAN PENGARUHNYA TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR - I Wayan Tantra; Ni Made Viviyani; Gusti Ayu Mahanavami (JUIMA : JURNAL ILMU MANAJEMEN, 2020)
This study aims to determine the significance of the effect of partial variable companies growth, profitability and firm size companies on the capital structure of Manufacturing companies (food and beverages sub sector) on the Indonesia Stock Exchange in the sampling was done by purposive samoling method, with a total sample 12 companies. To solve the problem in this study used multiple linear regression analysis technique using the help of SPSS versi 22.0. In partial results of the study (t test) with significance level 5% program indicating that the company growth has no significant effect on the capital structure, profitability has a significant affect on capital structure and firm size has no significant effect on capital structure in manufacturing companies (food and beverage sub sector) on the Indonesia Stock Exchange for the period 2015-2018.